Short-term culture of adult bovine ovarian tissues: chorioallantoic membrane (CAM) vs. traditional in vitro culture systems - Kylie Beck; Jaswant Singh; Mohammad Arshud Dar; Muhammad Anzar (BMC, 2018)
Abstract Background A suitable culture system is important for follicle growth in adult bovine ovarian tissue. This study aimed to assess the avian chorioallantoic membrane (CAM) for short-term culture of adult bovine ovarian tissues compared with a traditional in vitro culture system. Methods Ovarian cortical tissues (1-2 mm3), collected from slaughtered adult cows, were randomly assigned to control, CAM or in vitro culture groups. In the control group, ovarian tissues were fixed with paraformaldehyde without culture. In CAM and in vitro culture groups, the ovarian tissues were cultured for up to 5 days and then fixed. Ovarian tissues were examined on culture days 0, 1, 3 and 5 for angiogenesis, follicle morphology and growth. In all groups, primordial and growing (healthy and atretic) follicle densities were determined. Results In the CAM culture, the avian blood vessel density increased (p < 0.01) over time with a decline (p < 0.001) in the bovine blood vessel density. Healthy primordial, atretic primordial and healthy growing follicle densities were higher (p < 0.05) in CAM-cultured ovarian tissues than in vitro-cultured tissues. Regardless of the culture system, the density of healthy primordial follicles decreased (p < 0.001) over time with an increase in healthy growing follicles on day 3 (p < 0.01) and an increase in atretic (primordial and growing) follicles during the 5-day culture period (p < 0.001). The proportions of healthy primordial and atretic growing follicles were also affected by culture day (p < 0.001). Conclusions The CAM culture in chick embryos supported the bovine ovarian tissue grafts for 3 days demonstrating that CAM can be used as a satisfactory short-term culture system to assess ovarian tissue health, and to study follicle activation and development.